THE CONCEPT OF SOCIO-GEOGRAPHICAL SYSTEM AS A METHODOLOGICAL CONSTRUCT OF HUMAN GEOGRAPHY - Нємець, Костянтин; Нємець, Людмила (Human Geography Journal, 2015)
The article deals with the features and properties of sociogeosystem. It is shown that this concept is introduced to the scientific revolution from the position of socioaktogenezis. Sociogeosystem consists of mineral, biotic and social subsystems that are result of the planet development at different times. It is shown that in general terms all interactions in sociogeosystem reduced to information exchange between the major subsystems. Exchange of information in society is carried out through the executive system. Adaptive capacity of subsystems is defined by ratio of determined and stochastic processes. The main function of the global sociogeosystem is to convert structural information of natural subsystems in scientific information. It is shown that spatial mismatch of boundaries of social and natural subsystems in sociogeosystem taken into account depending on the purpose of investigation of spatial structure.